THE “STRANGER KINGS” IN RITA CHOWDHURY’S CHINATOWN DAYS: A STUDY - Rimjim Boruah , Rajashree Boruah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Marshall Sahlins talked of the prospect of stranger kings to narrate the succession of the authority especially in the Fiji islands and asserted that great kings or monarchs of the once prominent kingdoms or societies had been always a ‘stranger’ king. But in this paper I would like to suggest that the select theory could be elongated a bit and be related to various sort of rulers or leaders apart from the ‘kings’, it would be applicable also to those who had not been the kings in the literal sense yet possessed power and authority, holding a position of control over a certain group of population. The book Chinatown Days had introduced some such characters who were not the ‘kings’ but possessed the utmost traits of the stranger kings. I would like to apply Sahlins’ stranger king theory to noted Assamese writer Rita Chowdhury’s translated text “Chinatown Days”.